PHILOSOPHICAL-ANTHROPOLOGICAL JUSTIFICATION FOR PHYSICAL EDUCATION IN AND OUTSIDE OF SCHOOLS (Fiep Bulletin - online, 2014)
Worldwide there are problems with the realisation of sufficient school sport. It seems that the situation can only be improved, if the consciousness of the people involved in education can be changed towards the acceptance of more physical education as part of  education not to be neglected. There are well conceptualised justifications for school physical education which have been reported by research. They relate to dangers if no motor activity takes place and argue from a preventive and mainly curative point of view with a quasi “negative” connotation. By taking the road of philosophy-anthropology this analysis offers arguments for a justification by looking at the essence of the human being also as species made up for movement. Six philosophical theories (Grupe, 1982; Bielefeld, 1986, Röthig, 1970; Gigerenzer, 1981; Haag, 1989; Haag, 1986) will be presented under the aspect to what extent they contribute to a justification of physical education from an anthropological point of view. Questions like What is the human being? Is movement part of the behaviour of human beings? Have a positive outlook as opposed to the use of physical education as the “repair shop of the nation”. As a result of this analysis it can be stated that by using “negative” (mainly medial) and “positive” (mainly philosophy) approaches the position for justification of school physical education is quite strong and adequate to the field of sport, sport education, and sport science.
Keywords: physical education; in of school; outside of school; philosophical-anthropological justification